A 12-month retrospective study of outcomes of COVID-19 drive-through swabbing hubs’ screening of asymptomatic population in Qatar - Mohamed G. Al-Kuwari; Mariam A. Abdulmalik; Azza M. Mohammed; Shaikha Abushaikha; Mujeeb C. Kandy (Journal of Global Health Reports)
# Background